1980
DOI: 10.1055/s-2008-1074862
|View full text |Cite
|
Sign up to set email alerts
|

Celerin, a New Coumarin from Apium graveolens

Abstract: The isolation of cclcrin, LI ncw coumari~l from chc petrol extrncr of A p b m graveolens sccds is rcporred.As a part of our programme for the systematic chemical investigation of some Indian medicinal plants, we reported [I-31 the isolation of several coumarins from Apiurn graveolens LINN (Apiaceae) seeds commonly known as celery seeds. The present communication deals with the isolation and structural elucidation of another new coumarin, celerin (I), from the petrol extract of the seeds. Spectral studies of I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…villosum and H . tenue.2s2 The known 7-prenyloxy-8methoxycoumarin (289) has been given the trivial name lacinartin, and the optically active epoxide, lactinartinepoxide (290), and diol, lacinartindiol (291), both of unknown absolute configuration have also been isolated from Artemisia laciniata leaves. 283…”
Section: Have Been Isolated From Cononcliniopsis P R a ~I I J I O L I...mentioning
confidence: 99%
“…villosum and H . tenue.2s2 The known 7-prenyloxy-8methoxycoumarin (289) has been given the trivial name lacinartin, and the optically active epoxide, lactinartinepoxide (290), and diol, lacinartindiol (291), both of unknown absolute configuration have also been isolated from Artemisia laciniata leaves. 283…”
Section: Have Been Isolated From Cononcliniopsis P R a ~I I J I O L I...mentioning
confidence: 99%
“…In this study, we proved that the Indian celery seeds containing coumarin derivatives (1-9) are not derived from A. graveolens by using genetic and phytochemical approaches, even though Indian workers reported that A. graveolens seeds contain these compounds [2][3][4][5][6][7][8][9][10]. Furthermore, our results strongly suggested that the seeds were derived from S. diffusum based on their ITS sequences, characteristic components and distribution area.…”
Section: Discussionmentioning
confidence: 56%
“…The contradicting constituents of celery seeds reported by the Indian [2][3][4][5][6][7][8][9][10] and the Japanese researchers [11] are possibly due to the indiscriminative handling of celery and celery-related seeds in Indian (and also Pakistani) crude drugs/spices markets. The contradicting constituents of celery seeds reported by the Indian [2][3][4][5][6][7][8][9][10] and the Japanese researchers [11] are possibly due to the indiscriminative handling of celery and celery-related seeds in Indian (and also Pakistani) crude drugs/spices markets.…”
Section: Introductionmentioning
confidence: 98%
“…In this vein, two coumarins with the molecular formulas C 15 H 16 O 4 and C 14 H 14 O 3 were characterized as celerin (4) and osthenol (5) based on the mass ion peaks at m/z 261.112 [M + H] + and 231.101 [M + H] + , respectively. These compounds were reported among the formerly isolated phytoconstituents from A. graveolens seeds [ 38 , 65 , 66 ]. Another coumarin with the molecular formula C 11 H 8 O 4 was characterized as 6-acetyl-7-hydroxy-2H-1-benzopyran-2-one (6), in line with the mass ion peak at m/z 203.033 [M-H] − ; this molecule had been formerly described from A. petroselinum [ 67 ].…”
Section: Resultsmentioning
confidence: 99%